Political cleavages in Brazil: a longitudinal dimension - Borba, Julian; Silva, Gregorio; Amorim, Lucas (Revista Latinoamericana de Opinión Pública, 2024)
The study investigates the persistence and evolution of political cleavages in Brazil, examining how differences in public opinion relate to value priorities (materialism and postmaterialism) and party preference for the Workers’ Party (PT). The empirical basis consists of data from five waves of the World Values Survey (1991, 1997, 2006, 2014, and 2018), analyzed using factor analysis and item response theory techniques. The results reveal a value difference of the liberal-fundamentalist type that remains constant over the waves, with fundamentalist voters being more materialistic and less likely to prefer the PT. Additionally, it is observed that the relationship between this liberal-fundamentalist difference and the preference for the PT has become less stable over time, reflecting changes in the party’s base. These findings highlight the significant role of religious mobilization in Brazil and evidence historical roots in Brazilian public opinion that help to understand contemporary phenomena. By providing empirical evidence from the Brazilian context, the study contributes to the broader literature on political cleavages and suggests new directions for comparative research in other Latin American countries.